Effect of the percentage of Bos taurus inheritance on the fertility of Holstein×Zebu and Brown Swiss×Zebu crossbred cows in the Mexican tropics - Ríos-Utrera, Ángel; Zárate-Martínez, Juan P.; Vega-Murillo, Vicente E.; Enríquez-Quiroz, Javier F.; Montero-Lagunes, Maribel; Barradas-Piña, Francisco T.; Valdovinos-Terán, Martha E. (Revista Colombiana de Ciencias Pecuarias, 2022)
Background: No dairy breed or crossbreed has superior overall performance in all environments; therefore, it is necessary to determine which crossbreed is the most suitable for the Mexican tropic and what proportion of European breed is optimum for reproduction. Objective: To assess the effect of the proportion of Bos taurus (Bt) genes on reproductive performance of Holstein×Zebu (HZ) and Brown Swiss×Zebu (BZ) cows, and compare reproductive performance of these genotypes in a dual-purpose production system. Methods: Cows were maintained in a rotational grazing system on African star grass (Cynodon plectostachyus) in Veracruz, Mexico. Cows were milked twice daily. Calves were kept tied to the side of their dams while the cows were milked. Results: The percentage of Bt genes did not affect (p>0.05) fertility traits (age at first calving, days to first service after calving, services per conception, conception rate at first service, days open until conception, gestation length, and calving interval) of BZ cows. In contrast, HZ cows with less than 75% Holstein (H) genes were 0.3 years younger (p<0.05) at first calving and had 39.8 fewer days open (p<0.05) than HZ cows with 75% H genes or more. In addition, the calving interval of HZ cows with less than 75% H genes was 44.8 days shorter (p<0.05) than that of HZ cows with 75% H genes or more. The HZ cows had five fewer days pregnant and were 22.8 kg heavier at calving (p<0.05) than BZ cows. Conclusions: The effect of the percentage of Bt genes on cow fertility depends on the dairy breed used. In general, BZ and HZ cows present similar reproductive performance.